Analytical Study of Some Attack Tactical Principles For The Iraqi National League Participating in the Qualifying Asian Finals For The World Cup 2018 - Kadhim, Naji; Jarullah, Shaker (Journal of Physical Education, 2018)
Analytical Study of Some Attack Tactical Principles For The Iraqi National League Participating in the Qualifying Asian Finals For The World Cup 2018The research indicates the importance of revealing the real level of the Iraqi team participating in the Asian qualifying finals for the 2018 football World Cup. By diagnosing strengths and weaknesses of some offensive tactic principles that shows the development in Iraqi team performance level. The problem of the research lies in the fact that most of the national team coaches do not give much importance to the process of game tactics, especially during Iraqi teams participation in foreign championships, so the researcher decided to study this problem in order to identify the real reality and try to develop appropriate solutions. After reading Naji Kazem and Fares Sami Study published in the third scientific conference of the College of Physical Education and Sports Science 2017, which contains (18) tactical principle divided into (9) principles of offensive tactics and (9) principles of defensive tactics. A form was designed to analyze attack tactical principles.  The researcher used the descriptive method in the survey method based on the observation and analysis of some of the offensive tactics principles of the Iraqi national team in the Asian qualifying finals for the 2018 World Cups. The results obtained by the researcher show that the failed attempts were higher than the successful attempts as well as in   in changing the direction and passive possession of the ball was the highest   proportion of the positive possession this negatively affects the results of matches. Finally the researcher recommended developing offensive tactics, paying attention to individual and team tactical preparation for the Iraqi national league and compressive preparation of skills, physical, tactics and psychological through which the basic components of football can be integrated to reach a better level for the Iraqi team.